Biomass Composition and Sludge Production Estimation in Sequencing Batch Reactor (SBR) - Nelson, Sharon; Saranya, Thakre (Journal of Progress in Civil Engineering, 2025)
This study focuses on estimating biological sludge production in the Sequencing batch reactors (SBR) based wastewater treatment plants of India. It includes the different criteria for analyzing the specific sludge production in nine pre-anoxic selectors attached SBRs of India. The parameters generally vary with the geographical distribution of WWTPs (including living standard of the nearby population, its size, and working background), and also system's Solids Retention Times (SRT) play a significant role. The plants could perform biological nutrient removal (BNR), along with organic matter and suspended solids removal by satisfying the new NGT standards for COD, BOD, and TSS exceptionally. Biomass composition of the sludge in the treatment plants presented that the highest heterotrophic biomass and inert fraction were observed in the Varanasi SBR, 34%, and 58%, respectively. However, the range of heterotrophic biomass, cell debris, nitrifying biomass, non-biodegradable VSS, and Inert fractions were found 20-34%, 2-3%, 1-2%, 3-45%, and 28-58%, respectively in all the treatment plants. Wastewater characterization was also performed and showed that rbCOD/ COD range in the treatment plants varied from 8-32%. The readily biodegradable portion of COD is effective in denitrification and phosphorus release mechanisms of BNR processes of the pre-anoxic selector attached SBR plants.